PERBAIKAN CITRA RGB DENGAN METODE HOMOMORPHIC FILTERING MENGGUNAKAN BUTTERWORTH FILTER - Rizky, TM Irsan; Hasibuan, Nelly Astuti; Syahputra, Rian (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The photo is made into a visual recording that has historical value or a memento. However, many memorable photos no longer look good and have noise due to the effectiveness of nature such as the evaporation of liquid that is around the image, it can also be dust or water on the surface of the image, besides that the noise can also be caused by plastic and paper materials that contained in the place where the image is stored as a photo album. For noise caused when taking digital images from camera devices can be in the form of a smoke or light coil that causes the image display is not clear. When the process of capturing RGB images often encountered noise such as black spots. Noise can be improved with several image enhancement techniques such as smoothing, leveling, and convolution. One of the improvements in noise in digital images can be done with Homomorphic filtering Method. Image improvement using the Homomorphic filtering method followed by Butterworth Filtering is part of the discrete fourier transform algorithm which confirms a concept that is rarely used to improve RGB images. However, this can be proven in the form of testing to eliminate noise in improving the quality of RGB images..Keywords: image, homomorphic, butterworth, filtering, RGB, noise